Lessons from Rwanda (Journal of Comparative Social Work, 2007)
Before a recent visit to Rwanda, all that the country held for me, as with most people, was the spectre of genocide, war, poverty and starving children. My brief visit to the city of Kigali challenged my widely held assumptions about the country. Kigali was the epicenter of the genocide in Rwanda, where about one million people experienced murderous tyranny within a space of 100 days, that wreaked havoc upon the country and left millions of people with untold losses and emotional scars. Rwanda is, indeed, an amazing example of a country rising from the ashes. My first encounter was on the Air Rwanda flight, where the in-flight magazine warns those entering the country to leave their plastic bags behind; that no person would be allowed to pass through immigration and customs with plastic bags and wrappings. A plastic bag free country is one of Rwanda’s contributions to environmental conservation and saving the earth. And of course in stores, its paper bags all the way!